Uji Aktivitas Penghambatan Enzim α–amilase oleh Ekstrak Herba Ciplukan (Physalis Angulate L) Secara In Vitro - Lulu Alda Alfiani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Diabetes mellitus is a disease with metabolic disorders characterized by increased blood sugar levels that exceed normal limits. In 2019 people with diabetes mellitus reached 463 million people. In Indonesia, the number of people with diabetes mellitus experienced 8.5%, while in 2013, the number of sufferers was only 6.9%. Diabetes mellitus is divided into several types, one of which is type 2 diabetes mellitus. This type of diabetes is more common because this type of diabetes reaches 90-95% of the population with diabetes mellitus. In treating diabetes mellitus, pharmacological therapy that can be used is a synthetic drug, namely acarbose. Acarbose has the activity of inhibiting the action of the α-amylase enzyme. The enzyme α-amylase works by catalyzing the formation of starch into glucose by binding to 1,4 glycosidic bonds in starch. The Ministry of Health of the Republic of Indonesia said that 69.9% of Indonesians trust and utilize traditional health services. Ciplukan herb is one of the plants in Indonesia and is easily found in rural areas. This type of research was carried out by experimental laboratory research, which aims to determine the inhibitory activity of the α-amylase enzyme on the ethanol extract of the ciplukan herb. The α-amylase inhibition test was carried out using a UV-Vis spectrophotometer, and the absorbance was read at a wavelength of 400-800 nm. The α-amylase inhibition test by acarbose and samples was carried out by varying the concentration of acarbose, namely 100, 250, 500, 750, and 1.000 ppm, and the value was calculated. The results were obtained at 241.32 ppm acarbose and 735.45 ppm ciplukan herb extract. So it can stat that the inhibitory activity of the α-amylase enzyme in acarbose is greater than that of the extract.